Question

How do we find the LCM

x+3,x^2-9,x^(2)+6x+9

Step 1

The method to find the LCM *x*+*3*, *x²*-9, and *x²+6**x*+9.

To find the LCM., First find the factors of the given expression then find product of common factors and the rest of the factors.

Step 2

The factors of the polynomial *x²+6**x*+9...

Tagged in

Q: Solve the exponential equation by expressing each side as a power of the same base and then equating...

A: We use 4=2^2 and 8=2^3

Q: Evaluate:

A: The logarithmic expression is,

Q: Find the inverse function of the following: h=f(t)=96t-16t^2

A: It is given that the function h = f(t) = 96t – 16t2.Obtain the inverse of f(t) = 96t – 16t2 as follo...

Q: Graph the solution to the following system of inequalities. x-5 yz-4 3x+4y8 10 6 ? 4 -10 -8 -6 6 10 ...

A: Given information:The system of equation is shown below:

Q: 125=(5u+8)2

A: Consider the given equation

Q: (1/12x4+5/8x3+5/8x2+4)+(-7/12x4+3/8x2-4)=

A: Firstly, we remove the brackets and then we collect the like terms and solve as shown on board.

Q: X2=10x+10 How do I complete the square in the above problem?

A: we are given a quadratic equation as

Q: If x^3=3x^2, then what is x using the Zero-Product rule?

A: Given that x3 = 3x2.

Q: Use properties of logarithms to condense the logarithmic expression. Write the expression as a singl...

A: We first use the exponent rule of logarithm. Coefficients become exponents.

Sorry about that. What wasn’t helpful?